REFRACTIVE INDICES OF BINARY MIXTURES: nC5-CN8 ALCANOS, CYCLOHEXANE AND ETHANOL WITH TOLUENE - Lama-Ramirez, R. (1999)
It has been experimentally determined refractive index of binary liquid mixtures toluene with n-pentane, n-hexane, n-heptane, cyclohexane and ethanol at ± 0.02 c 25.00 c. using precision refractometer Bausch & Lomb. The molar fraction of the more volatile component is determined with an accuracy of ± 0.0005 accuracy. The refractive index of each bit is set to polynomial equations by the method of least squares, based on the molar fraction of the more volatile component.